Cross-Cultural Communication in MNCs: Insights into Structural Barriers and Strategic Solutions – A Narrative Review - Aquarini (Indonesian Scientific Publication, 2025)
This narrative review examines the complex landscape of communication in multinational corporations (MNCs), focusing on intercultural and structural challenges that affect internal communication and organizational cohesion. The study aims to synthesize recent findings and evaluate the effectiveness of current strategies in overcoming barriers such as language differences, cultural misalignments, and hierarchical communication structures. Using a structured review approach, the research draws on peer-reviewed literature from Scopus, Web of Science, and Google Scholar, analyzing thematic insights from qualitative and quantitative studies published over the past decade. The findings confirm that intercultural communication challenges—particularly language barriers and cultural diversity—remain persistent in MNC settings. Additionally, hierarchical organizational structures inhibit information flow and reduce employee engagement. Notably, the dominance of English as a corporate language can both facilitate and obstruct communication depending on local employees' proficiency levels. However, digital communication platforms and adaptive strategies that consider local cultural contexts have shown promise in mitigating these issues. The discussion emphasizes the importance of revisiting organizational communication policies, encouraging flatter hierarchies, and investing in intercultural training. These measures are key to fostering inclusive, responsive, and effective communication ecosystems. This review contributes to the literature by bridging systemic insights with practical implications, suggesting that a balanced global-local communication approach is critical for organizational resilience in diverse international contexts.